Precision Healthcare of Type 2 Diabetic Patients Through Implementation of Haptoglobin Genotyping - Bale, Bradley F.; Doneen, Amy L.; Vigerust, David J. (Frontiers in Cardiovascular Medicine, 2018)
It is well recognized that there is a need for medicine to migrate to a platform of delivering preventative care based on an individual’s genetic make-up. The term, which encompasses this type of care, is precision medicine. The US National Research Council and the National Institute of Health both now support the concept of utilizing genomic information to enhance the clinical management of patients. The newest institute of the American Heart Association is promoting precision cardiovascular medicine. This organization calls for the incorporation of genetic information to improve the care of individuals at higher risk for cardiovascular disease (CVD). It is believed this type of precision healthcare will revolutionize management. This current attitude of some of the most respected institutes in healthcare sets the stage for the utilization of the haptoglobin genotype to guide precision management in type 2 diabetics (DM). The Hp genotype has been studied extensively in type II diabetes (DM). The Hp2 genotype is an independent risk factor for CVD in DM patients. Hp2-2 generates five times increased risk of CVD compared to Hp1-1 DM patients. The Hp2-2 genotype also increases the risk of CVD three-fold compared to those with the Hp2-1 genotype in DM. Data has also shown that carrying the Hp2-2 gene in DM compared to carrying a Hp1-1 genotype can increase the risk the microvascular complications of nephropathy and retinopathy. In addition, the Hp2 gene enhances post percutaneous coronary intervention (PCI) complications such as, in stent restenosis and need for additional revascularization during the first-year post PCI. Evaluating the Hp genotype in DM patients can enhance the predictability of CVD risk.